Stress Analysis on Tubesheet Referring to TEMA Standard - Krisdiyanto Krisdiyanto; Muhamad Naufal Fikri; Rahmad Kuncoro Adi; Ahmad Restian Adi Nugroho (Universitas Muhammadiyah Yogyakarta, 2021)
A heat exchanger is a device used to transfer heat without mass transfer. The equipment must be designed according to established standards. The standard that is widely used is the standardissued by TEMA (Tubular Exchanger Manufacturer Association). The results of the design of theheat exchanger with these standards are considered less efficient in terms of the material. Theefficiency of the material used can be analyzed by stress analysis on the components that withstand the force, and one of these components is the tube sheet. Stress analysis on tube sheets can use finite element-based software. The results of the research show that the tube sheet design that refers to the TEMA standard is relatively safe because the maximum von Mises stress is below the yield strength of the material used, while the overdesign value is rather significant because the average von Mises stress is also far below the yield strength of the material used.